Analytical and experimental study on repair effectiveness of CFRP sheets for RC beams - Fayyadh, M.M.; Razak, H.A. (2013)
This paper presents the results of both analytical and experimental study on the repair effectiveness of Carbon Fibre Reinforced Polymer (CFRP) sheets for RC beams with different levels of pre-repair damage severity. It highlights the effect of fixing CFRP sheets to damaged beams on the load capacity, mid-span deflection, the steel strain and the CFRP strain and failure modes. The analytical study was based on a Finite Element (FE) model of the beam using brick and embedded bar elements for the concrete and steel reinforcement, respectively. The CFRP sheets and adhesive interface were modelled using shell elements with orthotropic material properties and incorporating the ultimate adhesive strain obtained experimentally to define the limit for debonding. In order to validate the analytical model, the FE results were compared with the results obtained from laboratory tests conducted on a control beam and three other beams subjected to different damage loads prior to repair with CFRP sheets. The results obtained showed good agreement, and this study verified the adopted approach of modelling the adhesive interface between the RC beam and the CFRP sheets using the ultimate adhesive strains obtained experimentally. Â© 2013 Vilnius Gediminas Technical University (VGTU) Press.